Between commemoration and manipulation. The concentration camp in Jasenovac in Serbian memory and public space in the late 1980s and early 1990s - Sokulski, Mateusz (Balcanica Posnaniensia. Acta et studia, 2023)
The article discusses the question of the politics of memory in the public discourse of Serbia in the 1980s with regard to the crimes commited by the Ustasha regime against the Serbian population in Independent State of Croatia (NDH), during World War II. Particular attention is is paid to the case of the largest Ustasha concentration camp Jasenovac. The discussion on this topic was presented on the basis of the press from the second half of the 1980s and the early 1990s. The predominant number of publications emphasised that the Serbs suffered huge losses and that the crimes against the Orthodox population in the NDH were never punished. Discussions about the genocide, which was often described in Serbia as „forgotten”, referred to the political climate in the republic at the time. Leading Serbian politicians spoke sharply on the subject, and numerous scientific and quasi-scientific publications were published. The number of victims was manipulated. Moreover, a message about the „awakening of the Ustasha spirits” was developed in relation to Croatian national activities. Anti-Croatian rhetoric intensified with the introduction of the multi-party system in Yugoslavia (1989) and strengthening of secessionist aspirations in Croatia. The discussions concerning Jasenovac were developed in the context of the political crisis of the federation at the time and the aspirations of Serbian elites towards national unification of Serbs around martyrdom messages.